2021
DOI: 10.1186/s12943-020-01305-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AURKA in Cancer: molecular mechanisms and opportunities for Cancer therapy

Abstract: Aurora kinase A (AURKA) belongs to the family of serine/threonine kinases, whose activation is necessary for cell division processes via regulation of mitosis. AURKA shows significantly higher expression in cancer tissues than in normal control tissues for multiple tumor types according to the TCGA database. Activation of AURKA has been demonstrated to play an important role in a wide range of cancers, and numerous AURKA substrates have been identified. AURKA-mediated phosphorylation can regulate the functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
226
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(273 citation statements)
references
References 239 publications
5
226
0
Order By: Relevance
“…Mounting evidence have shown that AURKA is involved in the tumorigenesis and progression of multiple types of cancer including solid and hematological malignancies [61][62][63]. Meanwhile, a certain quantity of AURKA kinase inhibitors have been developed during the past decade, which suppress cancer cell proliferation, migration and invasion [61]. In our study, we identified several chemicals related with AURKA that against EOC, which may contribute to the development of novel potential drugs for the treatment of EOC.…”
Section: Kegg and Go Pathway Analysis For 5 Core Genesmentioning
confidence: 85%
See 1 more Smart Citation
“…Mounting evidence have shown that AURKA is involved in the tumorigenesis and progression of multiple types of cancer including solid and hematological malignancies [61][62][63]. Meanwhile, a certain quantity of AURKA kinase inhibitors have been developed during the past decade, which suppress cancer cell proliferation, migration and invasion [61]. In our study, we identified several chemicals related with AURKA that against EOC, which may contribute to the development of novel potential drugs for the treatment of EOC.…”
Section: Kegg and Go Pathway Analysis For 5 Core Genesmentioning
confidence: 85%
“…AURKA, as a family of serine/threonine kinases, localizes in mitotic spindles and centrosomes where it mediates mitotic process and chromosome stability [60]. Mounting evidence have shown that AURKA is involved in the tumorigenesis and progression of multiple types of cancer including solid and hematological malignancies [61][62][63]. Meanwhile, a certain quantity of AURKA kinase inhibitors have been developed during the past decade, which suppress cancer cell proliferation, migration and invasion [61].…”
Section: Kegg and Go Pathway Analysis For 5 Core Genesmentioning
confidence: 99%
“…In addition to PLK1, many Aurora-A downstream substrates have been identified and the functional roles of Aurora-A-mediated phosphorylation of the substrates have been extensively investigated in tumorigenesis [33]. For example, p53 is phosphorylated at multiple serine residues, which regulates its protein stability and transcriptional activity [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we treated our models with Alisertib (MLN8237), which inhibits Aurora kinase A and to a lesser extent Aurora kinase B at different concentrations (Figure 2E and Figure S3) [34,35]. All of the cell lines and some of the organoids were more sensitive to Alisertib than AZD1775, and the remaining organoids were at least as sensitive to Alisertib as to AZD1775 (Figure 2E and Figure S6A).…”
Section: Wee1 Inhibition Induces Upregulation Of Aurora Kinase Signaling In Tp53 Mutant Ucsmentioning
confidence: 99%
“…Since Alisertib targets both Aurora A and Aurora B kinases at different doses, we tested a subset of the cell lines for cell cycle arresting capacity and sensitivity to the Aurora A specific inhibitor MK5108 and the Aurora B specific inhibitor Barasertib (AZD1152) to determine if inhibition of one or both kinases was more effective (Figure S6B,C) [34,35]. Alisertib resistant HEC1B along with Alisertib sensitive ARK1, SPEC2, and AN3CA were treated with either MK5108 or Barasertib and harvested for cell cycle flow cytometry analysis at various timepoints post-treatment.…”
Section: Wee1 Inhibition Induces Upregulation Of Aurora Kinase Signaling In Tp53 Mutant Ucsmentioning
confidence: 99%